Development of Wood Apple Shell (Feronia acidissima) Powder Biosorbent and Its Application for the Removal of Cd(II) from Aqueous Solution - Ch. Suresh; D. Harikisore Kumar Reddy; Yapati Harinath; B. Ramesh Naik; K. Seshaiah; Annareddy V. Ramana Reddy (The Scientific World Journal)
A biosorbent was prepared by using wood apple shell (WAS) powder and studied its application for the removal of Cd(II) from aqueous solution by a batch method. The biosorbent was characterized by infrared spectroscopy, X-ray diffraction, scanning electron microscopy, and elemental analysis. WAS is principally made up of lignin and cellulose, containing functional groups such as alcoholic, ketonic, and carboxylic groups which can be involved in complexation reactions with Cd(II). The effect of experimental parameters like initial pH, contact time, metal ion concentration, and sorbent dose on adsorption was investigated. The optimum pH for biosorption of Cd(II) onto WAS was found to be pH 5.0 and the quantitative removal of Cd(II) ions was achieved in 30 min. The kinetic study showed that the biosorption process followed the pseudo-second-order rate. Experimental data were analyzed by Langmuir, Freundlich, and Dubinin-Radushkevich isotherm models. Desorption studies were carried out using HCl solution.